The Extent of Adopting Blue Ocean Strategy and its Role in Increasing the Market Share Exploring Research on Alhamraa’ Insurance Company - Jamal, Marwa; shorooqsabah (International Journal of Psychosocial Rehabilitation, 2019)
In the light of increasing competition among Insurance companies in addition to the great increase in the insurance companies number that reach to (32) private company until the end of (2018) .From that point the Blue Ocean Strategy emerge as a modern method to go to blue places free from competition .Thus this research aims to explain the extent of adopting Blue Ocean Strategy on the level of (increase , excluding , reduction , invention ) and increase market share .Thus the researcher examined the theory which provided that there is statistically significant relations between adopting the insurance of Blue Ocean Strategy and its dimension level and the increase of market share .The research conclude that there is relation and connection relation between Blue Ocean Strategy and market share PSR-9891.Also the researcher put some recommendations the most prominent is that the invention is considered one of the successful strategies an d the company has to encourage the employees according to inventive thoughts .